Peer support for youth suicide prevention: a scoping review protocol - Megan Kennedy; Carla T Hilario; Joyce Kamanzi; Lisa Gilchrist; Solina Richter (BMJ Open)
Introduction Youth suicide is a significant public health priority, and is the second leading cause of death among young people between 15 and 29 years of age. An emerging intervention in suicide prevention programming with youth is peer support. Although increasingly used in other settings, the evidence for peer support interventions in youth suicide prevention remains nascent. This article presents a protocol for a scoping review aimed at systematically mapping the current evidence on peer support for youth suicide prevention.Methods and analysis Arksey and O’Malley’s scoping review framework will guide the review methods. The search strategy will be developed with guidance from a health sciences librarian. Multiple databases (Medline, Embase, PsycINFO, Cumulative Index for Nursing and Allied Health Literature) and grey literature will be identified using terms related to peer support and youth suicide prevention. Publication date restrictions will not be applied. All identified records of published literature will be collated and uploaded to a systematic review management software, Covidence, for review and selection. Screening will be completed in duplicate by two reviewers using predefined inclusion and exclusion criteria. Conflicts during screening will be resolved by a third reviewer. The title and abstract screening and full-text review will be completed in Covidence. Two reviewers will complete data extraction from the selected records, using a tailored extraction form. Screening and data extraction will be completed between January and April 2021. A narrative summary will be completed to synthesise key findings as well as contextual information about the use of peer support interventions in youth suicide prevention programming.Ethics and dissemination The results will be disseminated through a community research report, presentations of findings at relevant conferences and academic publications of the scoping review protocol and results. The data used for this scoping review will be derived from published resources; therefore, ethics approval is not required for this study.